Cancer pain: way to overcome - Chowdhury, Mostofa Kamal (Bangladesh Journal of Medicine, 2023)
Cancers are among the leading causes of morbidity and mortality worldwide. Cancer itself or cancer treatment often causes pain which can affectthe quality of life. Cancer pain management is an essential part of cancer treatment and palliative care. Cancer patients may require pain management at any stage of their disease, not only at the end. Expert opinion and statistics from country experiences from numerous low-income countries, where treatment coverage is typically inadequate or non-existent, indicate that around 80% of cancer patients feel moderate or severe pain that lasts on average 90 days. As a result, cancer pain is a major source of avoidable unnecessary suffering. Cancer pain management plans often involve pharmacological and nonpharmacological therapies and psycho-social and spiritual support. Palliative care and pain management are critical components of Universal Health Care. The medical use of narcotic drugs is essential for the treatment of pain and suffering. Therefore appropriate provisions must be made to assure their availability for such purposes. Some obstacles exist that limit the appropriate management of cancer-related discomfort. Communication difficulties, lack of pain management training and education, ethnic/cultural/ religious disparities, opiophobia among health professionals and the general public, and restricted availability to opioids are the primary barriers to successful cancer pain treatment. To combat cancer pain and reduce the suffering of these incurable people, education and training of health professionals on cancer pain management, provision of suitable holistic supports, opioids should be made accessible and available, and general awareness development are some examples. All government and nongovernment players must come forward and work together to win this battle. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 187